Efficacy of intraumbilical vein Methylergonovine maleate on duration of third stage of labor - Thidarat Phromboot; Apichart Chittacharoen; Somsri Pitakkijronnakorn (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objective: To study the efficacy of intraumbilical vein Methylergonovine maleate on duration of third stage of labor.Materials and Methods: Eighty-four term pregnant women undergoing vaginal delivery at Ramathibodi Hospital without risk factors were randomly assigned to receive 1 ml of Methylergonovine maleate (0.2 mg/ml) plus 0.9%NaCl 19 ml (n=42) or 0.9%NaCl 20 ml (n=42) by intraumbilical vein injection within one minute after cord clamping. Placenta was delivered by control cord traction technique. The duration of third stage of labor and side effects at one hour later were analysed.Results: There were no statistically significant difference among 2 groups regarding age, gestational age, parity, birth weight, placental weight and estimated blood loss. The duration of third stage of labor in Methylergonovine maleate group showed no statistically significant difference in compare with 0.9% NaCl group (5.97±3.28 Vs 6.53±4.56 minutes respectively, P>0.05). No side effects were observed in both groups.Conclusions: Intraumbilical vein Methylergonovine maleate had no effected on the duration of third stage of labor.